Effective Behavior of Insects Pollinators of Flowers in Gadung Mango Clone 21 Variety - Wiwin Windriyanti; Ramadhani Mahendra Kusuma (Jurnal Ilmu Pertanian Indonesia, 2022)
Pollinating insects are referred as support services, namely services by the processes in the ecosystems that support human well-being by maintaining or enhancing ecosystem services. The availability of flowers, diversity, and behavior of visiting pollinator insects affect the effectiveness of pollination to increase the formation of fruit sets of mango plants. The purpose of this study is to observe the behavior of pollinator insects visiting the mango gadung clone 21 varieties and their effectiveness in increasing the formation of fruit sets. Research has been carried out on two flower seasons: March-May (Off season) and July-September (On season) 2020. Visiting behaviors observed were the number of visits per minute (foraging rate) and the length of visit per flower (flower handling time). Pollination effectiveness was measured from the number of fruit sets formed from the open flower panicles and confined with a tangerine gauze. The results of the study obtained seven species including Apis sp., Trigona sp., Xylocopa sp., Polistes sp. 1, Polistes sp. 2, Chrysomya sp., and Eristalis sp. Visits of pollinating insects on the highest number of mango panicle flowers were (31.69 ± 7.69) flowers / 60 seconds by Trigona sp insects, and the lowest numbers were (2.70 ± 0.67) flowers / 60 seconds by Eristalis sp. insects. The longest visits of pollinator insects on mango flowers were obtained by Eristalis sp for (25.3 ± 8.50) sec/individual/flower and the shortest visits were by Trigona sp for (1.8 ± 0.63) seconds/individual/flower. Insect pollination increases fruit formation by 267.5%. Keywords: insect visits, pollinating insects, fruit formation, gadung 21 varieties mango